Neoadjuvant treatment with lenvatinib and pembrolizumab in a BRAF V600E-mutated anaplastic thyroid cancer: a case report - Barbaro, Daniele; Forleo, Raffaella; Profilo, Maria Antonietta; Lapi, Paola; Giani, Carlotta; Torregrossa, Liborio; Macerola, Elisabetta; Materazzi, Gabriele (Frontiers in Endocrinology, 2024)
Background: Tirosin kinase inhibitors (TKIs) and immunotherapy have been proposed for advanced metastatic anaplastic thyroid cancer (ATC). We report a case of BRAF V600E-mutated ATC in which Lenvatinib (L) plus Pemprolizumab ( P) enabled neoadjuvant treatment.Case presentation: A male patient, aged 65 years, presented with a rapidly enlarging left laterocervical mass. Fine needle aspiration was suggestive of ATC. Surgical consultation excluded radical surgery .While awaiting the molecular profile analysis and considering the fast evolution of the disease, treatment with L and P was started. L was started at a dose of 14 mg daily and P was started at the standard regimen (200 mg every three weeks). After one month computerized tomography showed a reduction in the mass with almost complete colliquative degeneration and the carotid artery wall was free from infiltration .Radical surgery was performed. The histology confirmed papillary thyroid cancer (PTC) in the left lobe and ATC with extensive necrosis in left latero-cervical lymph-node metastasis. The margins were free of tumours (R0). BRAF V600E mutation was present in both PTC and in ATC. At the one year follow-up, the patient was free of disease.Conclusion: L and P in combination also appear to be effective as neoadjuvant treatment in BRAF V600E mutated ATC. Their use could be undertaken every time the opportunity presents for the complete resection of the cancer as soon as is possible. The middle dose of 14mg of L seemed to be well tolerated and effective.